Risk Management Practices Among Accommodation Facilities in Ormoc City - Polinar, Mark Anthony N.; Dadulla, Daffodel M.; Payao, Ronald B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to ascertain the degree of impact and likelihood of the various risks, as well as the risk management method implementation among lodging facilities. In addition, the study took into account the link between the likelihood and impact of the various risks. To achieve this goal, a quantitative method engaging in a descriptive approach was with 128 respondents from 30 establishments who got involved in the study from the top management to rank and file through a self-completed survey. The level of the risk management process among the establishments showed a "slightly high level" of risk management implementation that signifies vulnerability to risks and could be detrimental to the establishment. To ensure impacts are regulated and the likelihood of happening will be controlled numerous risks based on the risk spectrum need to be addressed, treated, watched for, and reviewed. The results also revealed no significant relationships between the various types of risks, except people risks, which had a slight but favorable association between its impact and likelihood, which caused the null hypothesis to be rejected. According to the study's findings, firms should not take any risks lightly, regardless of how serious or likely they are as long as they present a threat. If risks are not properly handled, they can exacerbate or escalate their impact or likelihood. Moreover, a risk management plan based on ISO 31000-2009 needed to be proposed to have a more structured and systematic process.